FGF21 acts in the brain to drive macronutrient-specific changes in behavioral motivation and brain reward signaling - Md Shahjalal H. Khan; Sora Q. Kim; Robert C. Ross; Florina Corpodean; Redin A. Spann; Diana A. Albarado; Sun O. Fernandez-Kim; Blaise Clarke; Hans-Rudolf Berthoud; Heike Münzberg; David H. McDougal; Yanlin He; et al. (Molecular Metabolism)
Objective: Dietary protein restriction induces adaptive changes in food preference, increasing protein consumption over carbohydrates or fat. We investigated whether motivation and reward signaling underpin these preferences. Methods and Results: In an operant task, protein-restricted male mice responded more for liquid protein rewards, but not carbohydrate, fat, or sweet rewards compared to non-restricted mice. When the number of responses required to access protein reward varied, protein-restricted mice exhibited higher operant responses at moderate to high response requirements. The protein restriction-induced increase in operant responding for protein was absent in Fgf21-KO mice and mice with neuron-specific deletion of the FGF21 co-receptor beta-Klotho (KlbCam2ka). Fiber photometry recording of VTA dopamine neurons revealed that oral delivery of maltodextrin triggered a larger dopamine neuron activation than casein in control diet-fed mice, while casein triggered a larger activation in low-protein diet-fed mice. This restriction-induced shift in nutrient-specific VTA dopamine signaling was lost in Fgf21-KO mice. Conclusion: These data suggest that the increased FGF21 during protein restriction acts in the brain to induce a protein-specific appetite by specifically enhancing the reward value of protein-containing foods and the motivation to consume them.